Particle-modified electrodes: General mass transport theory, experimental validation, and the role of electrostatics - Chen, L; Kätelhön, E; Compton, R (Elsevier, 2019)
We present general mass transport theory for cyclic voltammetry at electrodes that are partially ‘blocked’ with electrochemically-inactive particles. It is broadly applicable covering reversible, quasi-reversible, and irreversible reactions and is experimentally validated using the hydrazine oxidation where theory follows experiment in quantitative detail. We extend our analysis to explore the role of electrostatics in three further reactions where the voltammetry is startlingly altered by electrostatic effects: the reduction of hexaammineruthenium (III), the oxidation of ferrocenemethanol, and the oxidation of ferrocyanide.